Hubungan Karakteristik Internal dan Eksternal dengan Jaringan Komunikasi Petani Karet di Kelurahan Batu Bersurat Kecamatan XIII Koto Kampar - Ikhsan, Muhammad Ikhsan; Yulida, Roza; Restuhadi, Fajar (Politeknik Pertanian Negeri Payakumbuh, 2020)
In order to encourage rubber agribusiness activities, farmers need adequate information and reliable sources of information to achieve their goals. To meet information needs, farmers develop communication networks between farmers and their actors. This research aims to describe the sociogram of the communication network of rubber farmers in self-help patterns,and analyze the relationship between farmer characteristics and communication networks.This research conducted in Batu Bersurat Village XIII Koto Kampar District. The method used in this research is the census method and the study respondents were taken as many as 42 farmers. The results of this research indicate that the structure of the communication network formed in rubber farmers approached the radial personal networkstructure .Based on the correlation test results indicate that the characteristics of rubber farmers related to locall centrality are, extent of land tenure, cosmopolity, intensity of counseling, and number of sources of information. Correlation test results indicate that the characteristics of rubber farmers related to globall centrality are level of education, extent of land tenure, cosmopolity, intensity of counseling, and number of sources of information.Correlation test results indicate that the characteristics of rubber farmers related to betwenness are extent of land tenure, cosmopolity, intensity of counseling, and number of sources of information.